Functionally deficient TRPV6 variants contribute to hereditary and familial chronic pancreatitis. Issue 2 (28th December 2021) - Hamada, Shin; Masson, Emmanuelle; Chen, Jian‐Min; Sakaguchi, Reiko; Rebours, Vinciane; Buscail, Louis; Matsumoto, Ryotaro; Tanaka, Yu; Kikuta, Kazuhiro; Kataoka, Fumiya; Sasaki, Akira; Le Rhun, Marc; et al.
Abstract: The recent discovery of TRPV6 as a pancreatitis susceptibility gene served to identify a novel mechanism of chronic pancreatitis (CP) due to Ca 2+ dysregulation. Herein, we analyzed TRPV6 in 81 probands with hereditary CP (HCP), 204 probands with familial CP (FCP), and 462 patients with idiopathic CP (ICP) by targeted next‐generation sequencing. We identified 25 rare nonsynonymous TRPV6 variants, 18 of which had not been previously reported. All 18 variants were characterized by a Ca 2+ imaging assay, with 8 being identified as functionally deficient. Evaluation of functionally deficient variants in the three CP cohorts revealed two novel findings: (i) functionally deficient TRPV6 variants appear to occur more frequently in HCP/FCP patients than in ICP patients (3.2% vs. 1.5%) and (ii) functionally deficient TRPV6 variants found in HCP and FCP probands appear to be more frequently coinherited with known risk variants in SPINK1, CTRC, and/or CFTR than those found in ICP patients (66.7% vs 28.6%). Additionally, genetic analysis of available HCP and FCP family members revealed complex patterns of inheritance in some families. Our findings confirm that functionally deficient TRPV6 variants represent an important contributor to CP. Importantly, functionally deficient TRPV6 variants account for a significant proportion of cases of HCP/FCP.